Relationship Between Early Marriage and Mother’s Levels of Knowledge with Nutritional Status - M. Thonthowi Jauhari; Junendri Ardian; Novia Zuriatun Solehah; Tresia Ayu Saputri (Research and Development Center for Food, Nutrition and Public Health (P4GKM) LPPM UNS, 2024)
Early marriage still needs to be a concern due to the high incidence of cases and the impact it has on the health and nutritional status of toddlers. One of the long-term effects of early marriage is stunting, namely impaired growth and development in toddlers due to malnutrition. This study aims to explore the relationship between maternal age at marriage and nutrition knowledge levels with the nutritional status of toddlers. This research uses observational research with a cross-sectional design. The sample in this study was 48 mothers of toddlers with a history of early marriage. Data analysis used Spearman’s Rank test. The results showed that most of the mothers of toddlers married in their early adolescence (14 to 18 years), namely 29 people (60.4%). As many as 58.3% of toddlers have poor nutritional status, and 1.7% are in the good nutritional status category. The majority of mothers’ knowledge related to nutrition is lacking, as many as 24 (50%). There is a significant relationship between levels of a mother’s knowledge about nutrition and the nutritional status of toddlers with a p-value of 0.001. However, mothers who marry early need to increase their understanding of balanced nutrition in toddlers to prevent malnutrition. Future research needs to look at the nutritional status of toddlers based on the education level of mothers of toddlers who marry early, which may be one of the causes of malnutrition status in toddlers.